Marker Recycling in Candida albicans through CRISPR-Cas9-Induced Marker Excision - Manning Y. Huang (American Society for Microbiology, 2017)
ABSTRACT We describe here a new approach to marker recycling, a controlled sequence of steps in which a genetic marker is selected and then lost. Marker recycling is important for genetic manipulation, because it allows a single selection marker to be used repeatedly. Our approach relies upon the ability of the CRISPR-Cas9 system to make a targeted double-strand break in DNA and the expectation that a double-strand break within a selection marker may promote recombination between directly repeated sequences that flank the marker. We call the approach CRISPR-Cas9-induced marker excision (CRIME). We tested the utility of this approach with the fungal pathogen Candida albicans, which is typically diploid. We used two selection markers, modified to include flanking direct repeats. In a proof-of-principle study, we created successive homozygous deletions in three genes through use of the two markers and had one of the markers available in the final strain for further selection and recycling. This strategy will accelerate the creation of multiple-mutant strains in C. albicans. CRISPR-Cas9 systems have been applied to many organisms, so the genetic design principles described here may be broadly applicable. IMPORTANCE It is critical to be able to alter genes in order to elucidate their functions. These alterations often rely upon markers that allow selection for a rare cell in a population that has incorporated a piece of DNA. The number of alterations that can be accomplished is thus limited by the number of selection markers that are available. This limitation is circumvented by marker recycling strategies, in which a marker is eliminated after its initial use. Then, the marker can be used again. In this report, we describe a new marker recycling strategy that is enabled by recently developed CRISPR-Cas9 technology.